Bagaimana Meningkatkan Daya Saing Daerah? - Ika Sartika (Institut Pemerintahan Dalam Negeri (IPDN), 2021)
Improving national competitiveness and regional competitiveness is the mandate of the Act as a reference for the government in planning and implementing development. To increase regional competitiveness, regional potential is needed as the basic capital for development. Tasikmalaya City as an autonomous region is a division of Tasikmalaya Regency which was ratified by Law No. 10 of 2001 has abundant potential in various sectors. However, due to various limitations, this potential has not been utilized optimally, so that the competitiveness of Tasikmalaya City is still inferior to Banjar City, Cimahi City, and West Bandung Regency which are much younger. This paper will discuss further how to improve regional competitiveness through the potential of the City of Tasikmalaya. This research was conducted with a qualitative descriptive approach with reference to Porter's diamond model. Data collection techniques in this study were interviews with informants, namely stakeholders in the City of Tasikmalaya, documentation, and observation. There were 17 informants who were successfully interviewed. Qualitative data obtained from interviews and observations were then analyzed by means of tabulation and categorization according to research interests. The next analysis uses an industrial cluster approach so that it is more likely to design a strategy to increase the competitiveness of the City of Tasikmalaya. All tertiary sectors that have very rapid growth in the City of Tasikmalaya then function as core industries, which are further broken down into supplier industries, buyers, supporting industries, related industries, and supporting institutions. With the formation of industrial clusters for tertiary sectors that have high potential, which is equipped with the identification of actors and their respective roles, the increase in the competitiveness of the City of Tasikmalaya will be realized more quickly